O uso de modelos tridimensionais no ensino de embriologia humana: contribuição para uma aprendizagem significativa - Meira, Miriam dos Santos (2015)
The inherent complexity of development of a new human being, especially when related to a lack of teaching-learning resources, makes the process of teaching-learning in the area of Human Embryology often difficult and abstract. The possibility of using and/or producing three-dimensional concrete models is recognized as an alternative capable of promoting the understanding of the different stages of human embryogenesis. Trying to evaluate, qualitatively and quantitatively, the educational potential of such macroscopic tools, three-dimensional models were used as intervention in Human Embryology lessons concerning the discipline taught to the second semester of undergraduate Biological Sciences, at Federal University of Santa Maria (UFSM), RS. To collect data, a knowledge test with illustrated and, in most of cases, closed questions was applied three times, what consisted in a pre-test, a post-theory test and a post-intervention test. The knowledge test and the models used were referring to the first four weeks of human embryogenesis. The pre-test helped in the first moment to survey the prior knowledge of the sample on the topic and, in a second moment, as a reference for comparison with the results of subsequent applications. Qualitative analysis of the tests resulted in categories of responses and quantitative analysis, in frequencies of each category and average score. Such analysis showed that the performance of the sample in the post-intervention test was considerably higher than in previous applications, what means that intervention models contributed significantly to the process of teaching and learning of the sample, what resulted in a better acquisition of knowledge about human embryonic development. The evaluation made by the sample also contributed to this statement. In this sense, it s highlighted the importance of using such pedagogical alternatives in initial and continuing teacher training, so such tools may be effectively used at different levels of science teaching.